Property is dummy proof: An experiment - Oren Bar-Gill; Christoph Engel (Max Planck Institute for Research on Collective Goods, 2020)
Law is for humans. Humans suffer from cognitive limitations. Legal institutions can help humans by making these limitations irrelevant. This experiment shows that strong property rights serve this function. In theory, efficient outcomes obtain even without strong property rights. In a hypothetical world where cognitive ability is perfect, individuals would not engage in wasteful taking wars. A party would not take another's good, if she expects that the good will ultimately be taken back. By contrast, the large majority of experimental subjects takes a token good when interacting with a computer they know to maximize profit, and that has a symmetric ability to take the good back. Experience mitigates the inefficiency, but does not eliminate it; and in the real world relevant experience is often lacking. We show that cognitive limitations prevent weak property rights &m imperfectly enforced property rules and liability rules with low damages - from securing efficient outcomes. Strong property rights should be preferred, because they are dummy proof.
hdl:21.11116/0000-0005-8B94-7
Keywords: C91; D02; D47; D61; K11; 330; Property; Liability; Cost of Appropriation; Cognitive Limitations; Sophistication; Descriptive and Normative Beliefs